Effect of Transcutaneous Electric Nerve Stimulation on Pain after Total Knee Arthroplasty: A Blind Randomized Controlled Trial - Beckwée, David; Bautmans, Ivan; Lefeber, Nina; Lievens, Pierre; Scheerlinck, Thierry; Vaes, Peter (The Journal of Knee Surgery, 2018)
Transcutaneous electric nerve stimulation (TENS) has proven to be effective for postsurgical pain relief. However, there is a lack of well-constructed clinical trials investigating the effect of TENS after total knee arthroplasty (TKA). In addition, previous investigations reported that low- and high-frequency TENSs produced analgesic tolerance after 4 or 5 days of treatment. The aim of this study is to explore the effect of burst TENS on pain during hospitalization after TKA and to investigate whether burst TENS produces analgesic tolerance after 4 or 5 days of treatment. This stratified, triple blind, randomized controlled trial was approved by the University Hospital Brussels. Sixty-eight subjects were screened for eligibility before surgery; 54 were found eligible and 53 were included in the analyses. Patients were allocated to either a burst TENS or sham burst TENS group. TENS was applied daily during continuous passive mobilization. Knee pain intensity, knee range of motion, and analgesic consumption were assessed daily. Patients received burst TENS (N = 25) or sham burst TENS (N = 28). No significant differences in knee pain intensity were found between the groups (p > 0.05). Within the TENS and the sham TENS groups, the difference in knee pain before and after treatment did not evolve over time (p > 0.05). This study found no effects of burst TENS compared with sham burst TENS on pain during hospitalization after TKA.
Keywords: arthroplasty; knee; transcutaneous electric nerve stimulation